تأثير تنفيذ برنامج القيادة المدرسية التدريبي في أداء مهام مديري المدارس في سلطنة عمان - عامري، إبراهيم خلفان الشين (Kulliyah of Education, International Islamic University Malaysia, 2021)
This study aimed to identify the degree of school leadership program effect on the performance of school principals' tasks in the Sultanate of Oman. To achieve the objectives of the study, a descriptive method was used. A questionnaire consisted of 32 items in three dimensions were used to collect data from the sample of the study where 186 participants responded. To answer research questions, mean, standard deviation, t-test, one-way ANOVA, and Scheffe test were utilized. The main findings of the study showed that the degree of school leadership program effect on the performance of school principals' tasks was at the moderate level. The results also indicated that gender and experience have statistically significant differences (α≤0.05) in the degree of school leadership program effect on the performance of school principals' tasks. In gender, female principals revealed higher impact than male, whereas in experience, principals with higher experience indicated higher effect compared to those with less experience. On the contrary, educational qualifications did not indicate statistically significant differences in the degree of school leadership program effect on the performance of school principals' tasks. Based on the results of the study, a number of recommendations were presented. One of the main recommendations was to review the training dimensions of school leadership program that were related to the development of technical, organizational and human skills of educational leaders in schools to enable them to address deficiencies or weaknesses. Another main recommendation was a need for coordination and compatibility in the application of job performance evaluation forms between what is provided by the school leadership program and what is implemented in the educational field in relation to the evaluation process. It was also recommended to conduct a study for exploring the reasons of the observed low-level effect of the school leadership program on male principals' tasks. Moreover, the study recommended for the need to guide school leaders to take advantage of senior school principals who had long experience and undergone school leadership programs. Furthermore, the study recommended to enable the school principals with more authorities and capabilities to apply skills gained from school leadership programs. In addition, the relationship between school, local community and parents have to be activated and school principals have to be empowered with necessary capabilities to apply skills acquired from the school leadership program such as the availability of modern technologies and the availability of required school activities and training necessities.